2017
DOI: 10.9767/bcrec.12.2.805.235-242
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidative Depolymerization of κ-carrageenan by Ozone

Abstract: Depolymerization kinetics of κ-carrageenan by ozone treatment has been studied at various pHs and times. The purified κ-carrageenan with the initial molecular weight of 271 kDa was dispersed in water to form (1 % w/v) solution. Ozone with 80±2 ppm concentration and constant flow rate of 3 L.min -1 was bubbled into the κ-carrageenan solution. The experiments were conducted at pH of 3, 7, and 10 at different times (5, 10, 15, and 20 minutes) of ozonation. The viscosity of the solution was measured using Ubbelohd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Modelling the ozonation kinetic of polysaccharides is complex. Prasetyaningrum et al(2017) 33 proposed a kinetic model to explain the depolymerization of κ-carrageenan by ozone using viscosity data. In the present work, a model for the ozone-starch reaction in alkaline solution was proposed, being [St] (g/L) the starch concentration as a function of time, [St] 0 (g/L) the initial starch concentration and k St the kinetic constant for the reaction:…”
Section: Kinetic Modeling Of Starch Oxidation With Ozone In Basic Sol...mentioning
confidence: 99%
“…Modelling the ozonation kinetic of polysaccharides is complex. Prasetyaningrum et al(2017) 33 proposed a kinetic model to explain the depolymerization of κ-carrageenan by ozone using viscosity data. In the present work, a model for the ozone-starch reaction in alkaline solution was proposed, being [St] (g/L) the starch concentration as a function of time, [St] 0 (g/L) the initial starch concentration and k St the kinetic constant for the reaction:…”
Section: Kinetic Modeling Of Starch Oxidation With Ozone In Basic Sol...mentioning
confidence: 99%
“…The ozone treatment was assessed to be more efficient than UV irradiation, as Table 1 shows the individual kinetic rate constant of ozone to be 7.877×10 -5 min -1 at a dosage of 125 mg/L. However, a previous study by Prasetyaningrum et al [35] demonstrated value of 7.21×10 -5 min -1 at pH 10 and a temperature of 30 °C. Interestingly, a combination of UV/O3 has been affiliated with an increase in the kinetic rate constant value, which was reported as 1.924×10 -4 min -1 , using a treatment with 125 mg/L ozone and a UV lamp intensity of 40.00 mW/cm 2 .…”
Section: Kineticsmentioning
confidence: 99%
“…K-carrageenan can be depolymerized using various techniques, such as thermal depolymerization [6], acid-catalyzed hydrolysis [7][8][9][10][11], enzymatic hydrolysis [2], ozone oxidation [12], and ultrasound irradiation [13]. When a polysaccharide solution is subjected to an ultrasound irradiation, the ultrasound wave will cause a cavitation which consists of the nucleation, growth, and collapse of microbubbles.…”
Section: Introductionmentioning
confidence: 99%